Emergence and upstream flight of lotic mayflies and caddisflies (Ephemeroptera and Trichoptera) in a lake outlet, central Finland - Bagge, Pauli (Entomologica Fennica, 1995)
Temporal and spatial occurrence and upstream flight of lotic mayflies and caddisflies were studied by means of kick netting, slit traps and floating emergence traps in Lake Konnevesi and its outlet stream (Siikakoski), mainly in 1983. Twenty species of mayflies and 78 species of caddisflies were recorded. Clearly lotic mayflies in the material were Baetis subalpinus, Heptagenia sulphurea and Ephemerella mucronata, which occurred only in the stream samples. Females of lotic Baetis rhodani had a long distance upstream flight in the area and occurred frequently in the floating emergence traps especially in sandy littoral habitats of L. Konnevesi. Procloeon bifidum and Nixe joernensis, which in some regions occur mainly in streams, were frequently found in the stony littoral belt of L. Konnevesi. Most of the mayflies recorded in the area were univoltine, but Baetis rhodani and Centroptilum luteolum at least had two generations in 1983. Strictly lotic species among caddisflies were Ceratopsyche nevae, Hydropsyche saxonica, Halesus digitatus, Ceraclea perplexa, Ylodes detruncatus, Athripsodes commutatus and Hydroptila forcipata. These were mainly found in stream samples. A short distance upstream flight of females (c. 0.1-0.4 km) was observed in the populations of H. siltalai, Psychomyia pusilla and Oxyethira frici and a moderate distance flight (at least 0.6 km) by females of Hydropsyche pellucidula, Cheumatopsyche lepida and Polycentropus irroratus. The most abundant caddisflies of the stream Siikakoski (Brachycentrus subnubilus, Neureclipsis bimaculata, Rhyacophila nubila, Agapetus ochripes, Micrasema setiferum and Hydroptila cornuta) were frequently found also in floating emergence traps in the lake (3. 7 km from the rapids). Females of Brachycentrus, Neureclipsis and Rhyacophila favoured traps on sandy substrata while females of Hydroptila were usually found in the stony belt. In the trap material of Agapetus ochripes, males were more abundant than females. According to emergence data, all caddisflies recorded in the area were univoltine though the emerging period of several species such as Rhyacophila nubila and Neureclipsis bimaculata was long. Maximum emergence was observed in early June when brachycentrids were swarming and another peak in August when limnephilids and leptocerids were abundant.